2011
DOI: 10.1093/rpd/ncq579
|View full text |Cite
|
Sign up to set email alerts
|

Activity concentrations of natural radionuclides in the sediments of Ogun River, Southwestern Nigeria

Abstract: The concentrations of naturally occurring radionuclides in the sediments of the Ogun River in Southwestern Nigeria were measured using NaI(Tl) gamma-ray spectrometry. The measurements were made in an effort to better understand the spatial distribution of natural radioactivity and to form a database of radioactivity levels of the Ogun River. The total average activity concentrations of (40)K, (226)Ra and (232)Th in the sediment samples representing the whole Ogun River from the upper region through the middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
0
12
3
Order By: Relevance
“…The range of observed activity concentrations of all radionuclides measured are presented in Table 2. The average values of all the radionuclides measured in this study were higher than those reported for similar environments in the Niger Delta and Nigeria [13,14], as well as typical global averages [23].…”
Section: Activity Concentrations In Sedimentscontrasting
confidence: 67%
See 2 more Smart Citations
“…The range of observed activity concentrations of all radionuclides measured are presented in Table 2. The average values of all the radionuclides measured in this study were higher than those reported for similar environments in the Niger Delta and Nigeria [13,14], as well as typical global averages [23].…”
Section: Activity Concentrations In Sedimentscontrasting
confidence: 67%
“…Activity concentrations of 40 K in the Bonny estuary were higher than reported elsewhere in the Niger Delta and Nigeria [13,14], but there was no significant difference between the sample sites (p = 0.59). If anthropogenic inputs are significant in the Bonny estuary, they are widely distributed across the three sites.…”
Section: Activity Concentrations In Sedimentscontrasting
confidence: 65%
See 1 more Smart Citation
“…The knowledge of radionuclides distributions in the sediments acts an essential part in monitoring of environmental contamination and assessment of radiological hazard arising from natural sources. For this purpose, in the recent years many studies give an importance to the measurements of the activity concentrations of natural radionuclides and their hazard on human health [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Another research study used the same device and the same properties. Indoor and outdoor absorbed dose rates were measured in the select region of AL-Qizweenia Najaf in Iraq [10]. Many studies in the gamma field of background radiation were conducted in different cities of Iraq [11][12][13].…”
Section: Dosimetry Typementioning
confidence: 99%